2011
DOI: 10.1289/ehp.1002524
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Gestational Lead Exposure Increases Retinal Progenitor Cell Proliferation and Rod Photoreceptor and Bipolar Cell Neurogenesis in Mice

Abstract: BackgroundGestational lead exposure (GLE) produces novel and persistent rod-mediated electroretinographic (ERG) supernormality in children and adult animals.ObjectivesWe used our murine GLE model to test the hypothesis that GLE increases the number of neurons in the rod signaling pathway and to determine the cellular mechanisms underlying the phenotype.ResultsBlood lead concentrations ([BPb]) in controls and after low-, moderate-, and high-dose GLE were ≤ 1, ≤ 10, approximately 25, and approximately 40 μg/dL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…However, it has been reported that steel workers with short-term metal-rich particulate matter exposure within a week's duration had longer telomere length compared with baseline samples 31. Similarly, it has been recently demonstrated that low-level lead exposure could increase and prolong retinal progenitor cell proliferation, rather than apoptosis 32. Although our finding suggests that Pb at a certain level in blood (short-term Pb exposure) may increase telomere length, since BLB (β=−1.72) played a predominant effect on PWBTL, and the inpatient workers showed relatively high long-term Pb exposure doses, it would not be surprising that comprehensive consequence of lead exposure in the battery plant workers was telomere length shortening.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that steel workers with short-term metal-rich particulate matter exposure within a week's duration had longer telomere length compared with baseline samples 31. Similarly, it has been recently demonstrated that low-level lead exposure could increase and prolong retinal progenitor cell proliferation, rather than apoptosis 32. Although our finding suggests that Pb at a certain level in blood (short-term Pb exposure) may increase telomere length, since BLB (β=−1.72) played a predominant effect on PWBTL, and the inpatient workers showed relatively high long-term Pb exposure doses, it would not be surprising that comprehensive consequence of lead exposure in the battery plant workers was telomere length shortening.…”
Section: Discussionmentioning
confidence: 99%
“…The membranes were probed with anti-TLR4 (0.2 μg/ml, Santa Cruz Biotechnology) or anti-TLR9 (1 μg/ml, AbCam; Cambridge, MA) antibodies, then incubated with horseradish peroxidase-conjugated secondary antibody, and visualized with ECL Plus (GE Healthcare; Piscataway, NJ). The membranes were stripped and reprobed using a GAPDH antibody as previously described (Giddabasappa et al, 2011). Densitometry measurements were obtained from non-saturated blots and the pixel intensity was normalized to GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining of Mouse Retinal Sections-All tissue processing, image acquisition, and analysis procedures were as described (23)(24)(25). Central sections (10 m thick; three nonadjacent sections per slide) were located 200 -400 m from the optic nerve.…”
Section: Mutantsmentioning
confidence: 99%